2020
DOI: 10.1093/mnras/staa3585
|View full text |Cite
|
Sign up to set email alerts
|

Resonance sweeping by a decelerating Galactic bar

Abstract: We provide the first quantitative evidence for the deceleration of the Galactic bar from local stellar kinematics in agreement with dynamical friction by a typical dark matter halo. The kinematic response of the stellar disk to a decelerating bar is studied using secular perturbation theory and test particle simulations. We show that the velocity distribution at any point in the disk affected by a naturally slowing bar is qualitatively different from that perturbed by a steadily rotating bar with the same curr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…We demonstrated that the most intense migration appears at the epoch of the bar formation, which is followed by a rapid decrease in its pattern speed and migration of the bar resonances. We note that signatures of the bar deceleration have been potentially found in the Milky Way, by studying local stellar kinematics (Chiba et al 2019), thus making our proposed scenario particularly suitable for the Milky Way. Therefore, we suggest that the age of the youngest high-metallicity stars ([Fe/H] > 0.2−0.3) on nearly circular orbits in the solar vicinity should correspond to the age of the Milky Way bar.…”
Section: Discussionmentioning
confidence: 86%
“…We demonstrated that the most intense migration appears at the epoch of the bar formation, which is followed by a rapid decrease in its pattern speed and migration of the bar resonances. We note that signatures of the bar deceleration have been potentially found in the Milky Way, by studying local stellar kinematics (Chiba et al 2019), thus making our proposed scenario particularly suitable for the Milky Way. Therefore, we suggest that the age of the youngest high-metallicity stars ([Fe/H] > 0.2−0.3) on nearly circular orbits in the solar vicinity should correspond to the age of the Milky Way bar.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, it is well known that spiral modes in simulations can be transient, remaining stationary for only a few rotations (Sellwood & Carlberg 2014), and the response of the disc should be different during the period of rising or declining amplitude. The same can be true for the bar, whose amplitude and pattern speed can also grow or vary with time (e.g., Chiba et al 2021;Hilmi et al 2020).…”
Section: Introductionmentioning
confidence: 88%
“…However, even a few km s −1 , e.g. the current level of uncertainty, is enough to make it unclear which feature in the Solar neighbourhood kinematics arises from which resonance, and if the bar is slowing, then multiple features can be explained by the resonant sweeping of a single resonance (Chiba, Friske & Schönrich 2019).…”
Section: Introductionmentioning
confidence: 99%